Rethinking ai and big data in marketing strategy: emphasizing ethics through a sensemaking perspective - Wang, E.; Berthon, P.; Su, Y. (58th Hawaii International Conference on System Sciences, HICSS 2025, 2025)
The exponential growth of big data, driven by AI and machine learning technologies, underscores the need for an ethical and sustainable approach to data utilization. Using problematization methodology, we consider the assumptions underpinning Big Data and AI and reconsider them from a sensemaking perspective. Big data represents an enactment rather than an objective reality, and organizations play an active role in its adoption and use. Strategizing is driven by plausibility rather than accuracy, and big data generates a retrospection of the past rather than a prediction of the future. A sensemaking perspective serves as reality check for managers, emphasizing the necessity of long-term sustainability and societal well-being. By cultivating experiments for learning communities and incubating innovation, organizations can effectively leverage big data in marketing, fostering transparent, collaborative, ethical, and sustainable data practices. © 2025 IEEE Computer Society. All rights reserved.
Keywords: AI; big data; dept.mrk; ethical; sensemaking; sustainable